Perlindungan Hukum Terhadap Hak dan Kewajiban Pekerja di Indonesia: Tantangan dan Solusi - Anindya, Salma Elsa; Damayanti, Ratih (Media Hukum Indonesia (MHI), 2024)
This study aims to discuss the importance of understanding rights and obligations in employment relations in Indonesia. Employers are expected to protect workers' interests through counseling, coaching, and ensuring work safety, while workers must also understand their obligations. Although there are laws regulating workers' rights, such as Law Number 13 of 2003, there are still obstacles in its implementation, including culture and lack of awareness. Real action is needed from the government to strengthen regulation and supervision. Suggestions provided include increasing socialization of rights and obligations, improving regulations, and social security for workers, especially in the informal sector, to create fair and sustainable employment relations. Effective legal protection is needed to create social justice and ensure workers' rights are respected.